Comparing the summer diet of stone martens (Martes foina) in urban and natural habitats in Central Bulgaria. Issue 3 (2nd July 2016) - Hisano, M.; Raichev, E.G.; Peeva, S.; Tsunoda, H.; Newman, C.; Masuda, R.; Georgiev, D.M.; Kaneko, Y.
Abstract : Understanding whether and how carnivores can adapt to urbanised environments is becoming increasingly important, as human populations grow and undeveloped landscape is lost. The stone marten ( Martes foina ) is often found in urban habitats across continental Europe, due to its flexible foraging behaviour. We compare the utilisation of food types for martens living in villages in a more populated region with that of martens living in a less populated mountainous forest region, over the summer fruiting season (May–July) of 2013, inferred from the analysis of 310 faecal samples. Fruits were the primary food for martens in both regions, but comprised a significantly greater proportion of the diet in villages. Invertebrates and rodents were utilised significantly more in the natural habitat. Garbage and domestic animals were rarely exploited in either region; however, village-dwelling martens appeared to rely heavily on being subsidised by cultivated fruits grown in gardens and orchards, and along the streets. We conclude that the stone marten is able to succeed in urbanised regions of Central Bulgaria by exploiting cultivated food resources, attributable to its flexible and adaptable generalist diet.